Biochemical alterations in rohu, Labeo rohita (Hamilton, 1822) exposed to organophosphorus insecticide, methylparathion - Perumal, Siva; Sankar, T. V. (Indian Journal of Fisheries, 2013)
The effect of exposure to sublethal concentrations of methylparathion on enzyme activities in the liver of rohu, Labeo rohita, was studied during 96 h exposure. Alterations were observed in alanine aminotransferase (ALT), aspartate aminotransferase (AST), lactate dehydrogenase (LDH), alkaline phosphatase (ALP) and acid phosphatase (ACP) ) activities in the liver of L. rohita, of mean size 75 Â± 6 g. ALP and ASP activity levels in methylparathion treated fishes were significantly (p